EMPATHY IN JAPANESE HONORIFIC EXPRESSIONS: A LINGUISTIC AND CULTURAL ANALYSIS - Y.A. Sabirova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Empathy plays a central role in Japanese communication and is reflected through the honorific system (keigo). Beyond expressing respect, Japanese honorific expressions convey interpersonal sensitivity and cultural values such as omoiyari, wa, enryo, and the uchi-soto distinction. This study explores the relationship between empathy and keigo from linguistic, pragmatic, and cultural perspectives. Using a qualitative descriptive approach, it analyzes authentic Japanese conversations, educational materials, and previous studies, with a brief comparison to Uzbek politeness strategies. The findings show that Japanese honorific expressions function as a system of linguistic empathy, promoting harmonious interpersonal relationships. The study also highlights the importance of integrating empathy into Japanese language education for foreign learners.